Hidden Dynamics and Hybrid Synchronization of Fractional-Order Memristive Systems - Haipeng Jiang; Lizhou Zhuang; Cheng Chen; Zuolei Wang (Axioms, 2022)
A fractional-order memristive system without equilibrium is addressed. Hidden attractors in the proposed system are discussed and the coexistence of a hidden attractor is found. Via theoretical analysis, the hybrid synchronization of the proposed system with partial controllers is investigated using fractional stability theory. Numerical simulation verifies the validity of the hybrid synchronization scheme.